Homossexualidades nas pesquisas em pós-graduação em psicologia: da despatologização à luta por direitos - Sposito, Sandra Elena [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research investigated the thesis and dissertations produced in the ambit of postgraduation in Psychology in Brazil in the period from 1999 to 2010, which presented as main theme the homosexualities. The main objective was to identify relevant aspects of knowledge production about this theme, such as: main research centers, prevailing theoretical and methodological models, most frequent focus of studies, conceptions about the practice of the psychologist facing the demands raised by homosexualities. The theoretical perspectives adopted to transit through the field of homosexualities in Psychology were supported by Foucault and authors who dialogue with his work, and also the contributions of the gender studies. The Foucaultian genealogical methodology guided the investigative paths of this study, laying the foundations to the systematization of the data from the format of a state of art research, mapping a knowledge area from a temporal and thematic cutting. The results found indicated that the researches about the homosexualities are predominantly conducted in post-graduation programs located in the southeast/south axis of the country; in the period studied there was a growth in the number of thesis and dissertations about the theme; there are sub-themes related to homosexualities that stood out in the amount of researches, which are: the family-marital, the homosexual identity and the prejudice-discrimination. The analysis of the collected data indicated that the conceptions about homosexualities in Psychology did not present an essentialist bias, nor a biologizing one, and neither were guided by the investigation of the causes of the homosexual behavior or desire. There was a predominance of Foucaultian referential in what regards the sexuality from the concept of the apparatus of sexuality. It was also noticed a prevalence of references to the category of identity as a way to map, name...

Essa pesquisa investigou as teses e dissertações produzidas no âmbito da pósgraduação em Psicologia no Brasil no período de 1999 a 2010, que apresentaram como tema principal as homossexualidades. O objetivo principal foi identificar aspectos relevantes da produção de conhecimento acerca desta temática como: principais centros de pesquisa, vertentes teóricas e metodológicas predominantes, focos de estudos mais frequentes, concepções acerca da atuação do/a psicólogo/a frente as demandas suscitadas pelas homossexualidades. As perspectivas teóricas adotadas para transitar pelo campo das homossexualidades na Psicologia foram respaldadas por Foucault e autores que dialogam com sua obra juntamente com as contribuições dos estudos de gênero. A metodologia genealógica foucaultiana norteou os trajetos investigativos desse estudo, lançando as bases para a sistematização dos dados a partir do formato de uma pesquisa de estado da arte, mapeando uma área do conhecimento a partir de um recorte temporal e temático. Os resultados encontrados indicaram que as pesquisas sobre as homossexualidades são predominantemente realizadas em programas de pósgraduação localizados no eixo sudeste/sul do país; no período estudado houve um crescimento no número de teses e dissertações sobre o tema; há sub-temas relacionados às homossexualidades que se destacaram no volume de pesquisas, sendo estes: o familiar-conjugal, a identidade homossexual e o preconceitodiscriminação. A análise dos dados coletados indicou que as concepções acerca das homossexualidades na psicologia não apresentaram um viés essencialista, nem biologizante, bem como não se pautaram na investigação das causas do comportamento ou desejo homossexual. Houve uma predominância dos referenciais foucaultianos no que tange à sexualidade a partir do conceito de dispositivo da sexualidade. Também notou-se uma prevalência de...
Keywords: Homossexuais; Sexo (Psicologia); Identidade sexual; Homossexualidade - Despatologização; Sex (Psychology)